An experimental and numerical investigation of concrete pry-out failure after fire exposure: Group effects and failure mechanism. (1st September 2022) - Tian, Kaipei; Ožbolt, Joško; Jebara, Khalil; Chen, Jian-Fei
Highlights: After 60 and 90 min of ISO 834 fire exposure the pry-out failure load is reduced by about 70% and 80%, respectively. The group effect on shear stiffness is strong at ambient condition but moderated after fire exposure. The group effect on pry-out failure load is significant both before and after fire exposure. Microplane based thermo-mechanical model for concrete can simulate well the concrete pry-out failure mode before and after fire. Abstract: In the present study, the load-bearing capacity for concrete pry-out failure of the single stud anchor and multi-stud anchor groups after fire exposure is investigated experimentally and numerically. The main topic of the investigation is the influence of fire duration on the resistance and failure mode and the group effect on the load-bearing behaviour. The standard ISO 834 fire curve was employed. The numerical simulations were conducted using the thermo-mechanical model based on the microplane constitutive model for concrete, which was implemented into a 3D finite element (FE) code. The numerical model was first verified based on the performed experimental tests. Subsequently, the parametric study was performed in order to analyse the failure mechanism and the load distribution over the studs of the anchor group. It was shown that the employed numerical modelling technique can successfully predict the pry-out failure mode and the load-bearing behaviour of anchor groups after fire exposure. The results show that the group effect on the shear stiffness of anchors is strong at ambient temperature, but moderated after fire exposure. The group effect on the pry-out failure load of anchors, both before and after fire exposure, is significant. The evaluation of the load distribution at the interfaces between anchor and concrete contributes to a better understanding of the concrete pry-out failure mechanism before and after fire exposure.